2017
DOI: 10.1021/acs.langmuir.7b00588
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Growth of Copper Hydroxy Double Salt Films and Their Conversion to Nanostructured p-Type CuO Photocathodes

Abstract: New electrochemical synthesis methods were developed to produce copper hydroxy double salt(Cu-HDS) films with four different intercalated anions (NO, SO, Cl, and dodecyl sulfate (DS)) as pure crystalline films as deposited (CuNO(OH), CuSO(OH), CuCl(OH), and CuDS(OH)). These methods are based on p-benzoquinone reduction, which increases the local pH at the working electrode and triggers the precipitation of Cu and appropriate anions as Cu-HDS films on the working electrode. The resulting Cu-HDS films could be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 53 publications
2
53
0
Order By: Relevance
“…Previously, we have demonstrated that nanofibrous CuO electrodes can be prepared by using electrodeposited Cu 4 SO 4 (OH) 6 films as precursors. 54 The electrodeposited Cu 4 SO 4 (OH) 6 films are composed of blade-like nanocrystals due to the two dimensional crystal structure of Cu 4 SO 4 (OH) 6 ( Figure S14A). When immersed in 0.01 M NaOH solution (pH 12), they were converted to fibrous Cu(OH) 2 films ( Figure S14B), which could be converted to fibrous CuO films by annealing for 3 h at 500°C.…”
Section: Synthesis Of Cuo and Li-doped Cuo Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have demonstrated that nanofibrous CuO electrodes can be prepared by using electrodeposited Cu 4 SO 4 (OH) 6 films as precursors. 54 The electrodeposited Cu 4 SO 4 (OH) 6 films are composed of blade-like nanocrystals due to the two dimensional crystal structure of Cu 4 SO 4 (OH) 6 ( Figure S14A). When immersed in 0.01 M NaOH solution (pH 12), they were converted to fibrous Cu(OH) 2 films ( Figure S14B), which could be converted to fibrous CuO films by annealing for 3 h at 500°C.…”
Section: Synthesis Of Cuo and Li-doped Cuo Electrodesmentioning
confidence: 99%
“…In this study, we used oxygen reduction as the photoelectrochemical reduction reaction that occurs on the CuO surface as the kinetics of this reaction is typically much faster than water reduction on oxide-based photocathodes. [54][55][56][57] The J−V plots of CuO and Li-doped CuO for oxygen reduction obtained in a 0.1 M KOH (pH 13) solution purged with O 2 under standard illumination conditions (AM1.5G, 100 mW/cm 2 ) are shown in Fig. 5.…”
Section: Experimental Comparison Of Photoelectrochemical Properties Omentioning
confidence: 99%
“…Cardiel et al. synthesized CuO nanostructure from 2D Cu‐hydroxy double salt precursor which can generate photocurrent density of ∼1.5 mA/cm 2 at an applied potential of 0.6 V vs. RHE …”
Section: Introductionmentioning
confidence: 99%
“…Figure 4(iv) displays a typical thickness of 600 nm for γ‐WO 3 films. A possibly useful strategy is the so‐called nanostructuring, which can shorten the necessary traveling distance of minority carriers so that they reach the interface and consequently minimize the electron‐hole recombination 73 …”
Section: Resultsmentioning
confidence: 99%